FAKTOR SOSIAL EKONOMI TERHADAP MINAT MASYARAKAT MENABUNG DI DUSUN PANGKAH SABRANG KEC. PANGKAH KAB. TEGAL - Ery Suryanti; Hendra Lesmana; Husni Mubarok (Universitas Teuku Umar, 2021)
Abstract: Socio-economic factor is a factor that is indeed a factor in the surrounding community which affects the interest in saving. People with socio-economic groups who have income will have a lot of interest in saving, in contrast to people who do not have income because for people who do not have income the money they receive will be used for consumption or for daily living needs. Pangkah Sabrang Hamlet is a hamlet with 255 household heads, each of whom has a different work. The results of the study show that many of the people of Dukuh Sabrang have an interest in saving for reasons of the future, to buy assets, for tuition or school fees and for the precautionary costs of the research results 84% have savings in banks and 14% have savings in save for yourself and 2% have no savings. Data collection techniques through documentation, interviews and observations. Data analysis techniques used documentary research and descriptive analysis.